AN ANALYSIS OF THE RELATIONSHIP BETWEEN STUDENTS' SCIENTIFIC ATTITUDE AND STUDENTS' LEARNING STYLE IN JUNIOR HIGH SCHOOL - Nabilah Kinanti Putri, - (2018)
The objectives of this research were to profile the Scientific Attitude Level, Learning Style Preference, and the relationship between them in "X" Junior High School in Bandung. This research was conducted with survey research design by the total research sample of 110 students drawn from the population. There were two instruments employed in this research; Scientific Attitude Questionnaire and Visual, Auditory, and Kinesthetic (VAK) Learning Style Inventory. The Scientific Attitude Questionnaire contains five aspects of Scientific Attitude there are; Rationality, Curiosity, Open-mindedness, Aversion to superstition, and Objectivity. The VAK Learning Style Inventory constructed by three aspects that able to identify three sensory receivers such as; visual, auditory, and kinesthetic. Reliability value of the Scientific Attitude Questionnaire is .896 obtained by statistical procedure. The result shows that students are having Average Level of Scientific Attitude, students generally prefer Kinesthetic Learning Style, and there is a medium relationship between Students' Scientific Attitude and Students' Learning Style. For further research related to Scientific Attitude and Learning Style, especially in Junior High School level, it is highly recommended to apply more data collection technique in order to enrich the information resulted from the research. ;--- Tujuan dari penilitian ini adalah untuk mengetahui profil tingkat Sikap Ilmiah, pilihan Gaya Belajar, dan hubungan antar keduanya di Sekolah Menengah Pertama "X" di Kota Bandung. Penelitian ini menggunakan desain penelitian survei dengan jumlah sampel 110 orang siswa yang diambil dari populasi. Dua buah instrumen yang digunakan dalam penelitian ini adalah; Kuisioner Sikap Ilmiah, dan Kuisioner Gaya Belajar Visual, Auditori, dan Kinestetik (VAK). Kuisioner Sikap Ilmiah terdiri dari lima aspek Sikap Ilmiah yaitu; rasionalitas, rasa ingin tahu, keterbukaan pikiran, penolakan terhadap takhayul, dan objektivitas. Kuisioner Gaya Belajar VAK terdiri dari tiga aspek yang mampu mengidentifikasi tiga sensor penerima yaitu; sensor visual, sensor auditori, dan sensor kinestetik. Nilai kepercayaan Kuisioner Sikap Ilmiah yang diambil melalui prosedur statistik adalah .896. Hasil dari penelitian ini menunjukkan bahwa para siswa memiliki Tingkat Sikap Ilmiah Rata-Rata, pada umumnya para siswa memilih Gaya Belajar Kinestetik, dan adanya hubungan yang sedang diantara Sikap Ilmiah Siswa dan Gaya Belajar Siswa. Untuk penelitian selanjutnya, sangat disarankan untuk mengaplikasikan lebih banyak teknik pengumpulan data dengan tujuan untuk memperkaya informasi yang dihasilkan.